'I was in need of somewhere to release my hurt:' Addressing the mental health of vulnerable adolescent mothers in Harare, Zimbabwe, through self-help groups. Issue 1 (31st December 2022) - Chingono, Rudo; Kasese, Constance; Miles, Sam; Busza, Joanna
ABSTRACT: Background: Adolescents experiencing multiple vulnerabilities, including poverty, curtailed education, transactional sex and early childbearing, are at risk of poor mental health. In Zimbabwe, girls who are pregnant or new mothers and involved in selling sex struggle to cope with the combined pressures of parenthood, financial insecurity, and social stigma. A pilot intervention brought such girls together into self-help groups to increase peer support, resources and skills. Objective: This study aimed to explore whether and how participation in a self-help group intervention affected vulnerable young mothers' experiences and perceptions of mental health stressors. Methods: Self-help groups received 12 participatory sessions over 6 months. Eighteen semi-structured interviews and three focus group discussions were held with participants and drop-outs. Before and after the intervention, participants completed the locally validated 14-item Shona Symptom Questionnaire tool to indicate the probable prevalence of common mental health disorders. Results: Adolescent girls described mutually reinforcing stressors in their lives and reported low self-esteem and anxiety. Key themes emerging from qualitative data centred around girls' struggles with adverse life events, the burden of new motherhood, social isolation related to sex work and self-help groups as a source of hope. Participants joined groups to obtain support and felt their mental well-being improved due to new social networks, feelings of solidarity with peers, and increased confidence for positive action, that is, seeking health services for themselves and their babies. Prior to enrolment 16% showed signs of possible common mental disorders falling to 2% at follow-up. Conclusions: Participants believed involvement in interactive self-help groups improved their mental health by strengthening peer support and engendering hope for the future. Although reduced mental distress cannot be attributed to the programme, the pilot intervention offers a low-cost approach that could be rigorously tested and adapted to a wide range of community settings.